2012
DOI: 10.1186/1476-0711-11-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Allium sativum and Zingiber officinale extracts on clinically important drug resistant pathogenic bacteria

Abstract: BackgroundHerbs and spices are very important and useful as therapeutic agent against many pathological infections. Increasing multidrug resistance of pathogens forces to find alternative compounds for treatment of infectious diseases.MethodsIn the present study the antimicrobial potency of garlic and ginger has been investigated against eight local clinical bacterial isolates. Three types of extracts of each garlic and ginger including aqueous extract, methanol extract and ethanol extract had been assayed sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
87
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 24 publications
14
87
2
4
Order By: Relevance
“…To the best of our knowledge, this is the first study on extracts of plants to treat microbial infections in G. mellonella model, consequently there are no studies with similar methodology in order to compare and better discuss the present findings. Even so, these results agree with most published reports regarding the in vitro antimicrobial activity of ginger (19,20).…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, this is the first study on extracts of plants to treat microbial infections in G. mellonella model, consequently there are no studies with similar methodology in order to compare and better discuss the present findings. Even so, these results agree with most published reports regarding the in vitro antimicrobial activity of ginger (19,20).…”
Section: Discussionsupporting
confidence: 93%
“…Aqueous dilutions of the garlic extract showed better activity than the ethanol dilutions of the extract. Previous studies both support 28 and contradict 29 this finding; however, all studies do support the fact that aqueous extract preparations do result in antimicrobial activity. When comparing aqueous preparations of extracts to preparations using other organic solvents tested against B. cinerea, a parallel may be drawn between results from the present study and those achieved by Senhaji et al 27 , in that the present study revealed that complete (100%) mycelial inhibition could be achieved by using a 60% aqueous diluted extract (Table 1).…”
Section: Discussionmentioning
confidence: 87%
“…Hydrophilic leaf extracts of Juglans regia, bark of Salix albawasfound effective against E. coli, Staphylococcus aureus, Listeria monocytogenes, Bacillus cereus and Salmonella enteritis (Pop et al, 2013;Shah et al, 2013 Askari et al, 2013;Haouat et al, 2013;Das et al, 2012;Ayaz et al, 2016;Monika et al, 2014). Gull et al, (2012) Effect of aqueous plant extracts on incidence and severity of soft rot disease caused by Erwinia carotovora on stored potato tubers Among 13 plants tested in-vitro against the growth of Erwinia carotovora, three plant extracts showing highest efficacy with respect to growth inhibition are selected for this experiment. Best results were obtained when treatments were given 12 hours prior to inoculation or simultaneously with the inoculation of the pathogen than when treatments were given 12 hours after the inoculation of the pathogen ( Fig.…”
Section: Laboratory Evaluation Of Aqueous Plant Extracts Against the mentioning
confidence: 99%